For-profi t expansion and nonprofi t retraction in Brazilian higher education - Tagliari , Clarissa (Plural, 2022)
In this paper, we use microdata from the Brazilian Higher Education Census to compare the characteristics of courses that concentrated enrollment growth in the for-profi t and nonprofit institutions between 2010 and 2016. We analyze the trends observed in light of major regulatory changes, market dynamics and public policies to expand access to private higher education. The results indicate that the balance between organizational logics, regulation and public subsidies fostered quite different expansion patterns between for-profit and nonprofi t institutions, not supporting the interpretations that claim there is isomorphism in the off er of undergraduate courses in Brazil. Furthermore, the analyzes show that the performance of educational conglomerates can mean a strong shrinkage of nonprofit institutions.